PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP MOTIVASI BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Hazhari, Alvan; Sih Hika Pamungkas, Maya (Journal of Professional Elementary Education, 2025)
This study aims to determine the effect of the Talking Stick learning model on Social Studies learning motivation in grade V SDN Sukadalem 1 WaringinKurung, Serang Regency. The problem in this study is the low student motivation in social studies learning because the learning model used tends to be monotonous and teacher-centered. This type of research is a survey research using a questionnaire to determine student motivation. In this research, there were 40 respondents or samples who were fifth grade students of SDN Sukadalem 1 Waringinkurung. The results showed that there was an effect of the Talking stick learning model on the learning motivation of grade V SDN Sukadalem 1 Waringinkurung, Serang Regency. This is evidenced by the amount of t count of 9.625 and t table of 1.684. Sehungga Thitung> Ttabel which means Ha is accepted and Ho is rejected, which shows the influence of the Talking Stick learning model on learning motivation in the Social Studies subject for Class V SDN Sukadalem 1 Waringinkurung.